Thalamic Gangliocytoma in a Pediatric Patient—An Incidental Diagnosis - Oyuela-Mancera, Martha E.; Maturana, Jennifer R.; Rodriguez, Laura C.; Perez-Acosta, Juan J.; Rodado-Mieles, César E.; Bastidas, Nicolás (Journal of Pediatric Neurology, 2023)
Gangliogliomas and gangliocytomas are ganglion cell tumors that arise from the neuroepithelium. The most marked difference between both tumors is that gangliogliomas have a neoplastic glial component. At the same time, gangliocytomas comprise mature dysplastic ganglion cells with no neoplastic glial component. A 4-year-old male patient, a product of third gestation, was admitted to the emergency department after presenting obstructive bronchial symptoms secondary to viral infection with bacterial coinfection; during this condition, he accidentally fell from the crib (1-m high), with subsequent mild cranioencephalic trauma. A noncontrast cranial computed tomography showed a solid mass in the right thalamus and generated basal ganglion edema. A gangliocytoma grade II was confirmed by magnetic resonance imaging and histopathological result. Our unique case demonstrates an atypical location not previously reported in the pediatric population.
Keywords: gangliogliomas; gangliocytomas; MRI; thalamus